2016
DOI: 10.5194/nhess-16-1719-2016
|View full text |Cite
|
Sign up to set email alerts
|

Partial reactivation of a huge deep-seated ancient rock slide: recognition, formation mechanism, and stability

Abstract: Abstract. About 18 years ago, a large-scale discontinuous layer in properties and colour was found in the new Fengjie town at the shore of the Three Gorges Reservoir area in China. There are many resettled residents and buildings on the sloping area, the safety of which is potentially affected by this layer, so it has become the focus of attention. Before this study started there were two viewpoints regarding the origin of this layer. One was that is was from a huge ancient slide and the other was that is was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The absence of the phenomenon in the sand‐sized granules and, conversely, the occurrence of some slip‐weakening behavior—in the investigated displacement rate range and test duration—could be explained by the smaller pore size, which did not allow for sufficient mobility of the viscous mud but allowed the same mud to be sheared over long distances and time, making its thixotropic behavior apparent. Similarities in structure and composition between the experimentally obtained shear zones and those of landslides moving along bedding planes and within weak layers of saturated and weathered mudstone (e.g., Tang et al, ; Zhang et al, ), and the fact that such landslides can suffer dramatic acceleration due to a possible rate‐weakening mechanism (Q. Xu et al, ), suggest that the observed behavior might play a role in the kinematics of some landslides in mudstone layers.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The absence of the phenomenon in the sand‐sized granules and, conversely, the occurrence of some slip‐weakening behavior—in the investigated displacement rate range and test duration—could be explained by the smaller pore size, which did not allow for sufficient mobility of the viscous mud but allowed the same mud to be sheared over long distances and time, making its thixotropic behavior apparent. Similarities in structure and composition between the experimentally obtained shear zones and those of landslides moving along bedding planes and within weak layers of saturated and weathered mudstone (e.g., Tang et al, ; Zhang et al, ), and the fact that such landslides can suffer dramatic acceleration due to a possible rate‐weakening mechanism (Q. Xu et al, ), suggest that the observed behavior might play a role in the kinematics of some landslides in mudstone layers.…”
Section: Discussionmentioning
confidence: 68%
“…The mudstone granules were extensively crushed and damaged (Figures S3, S8, and S9 in the supporting information), similarly to what can happen in nonplastic granular soils (e.g., Fukuoka et al, ; Xu et al, ). Furthermore, as the mudstone contains high proportions of clay (Miao et al, ; G. Xu et al, ; Xu et al, ; Tang et al, ), a soft, high‐water content mud was formed in the shear zone during the tests in saturated condition, and filled the pores between the granules (Figure S4b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Three Gorges Reservoir Area (TGRA) has been a landslide-prone area since ancient times due to geological environment and precipitation. In addition, a large number of landslides reactivated after the impoundment of the Three Gorges Reservoir, such as the Qiangjiangping landslide, Shuping landslide and Baishuihe landslide [9][10][11][12]. These landslides are characterized by large areas and damage to property, such as causing cracks in roads and houses.…”
Section: Introductionmentioning
confidence: 99%